2003
DOI: 10.1207/s15374424jccp3201_02
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Processing Bias for Emotional Information Across Clinical Disorders: A Comparison of Attention, Memory, and Prospective Cognition in Children and Adolescents With Depression, Generalized Anxiety, and Posttraumatic Stress Disorder

Abstract: This study investigated theoretical claims that different emotional disorders are associated with different patterns of cognitive bias, both in terms of the cognitive processes involved and the stimulus content that is preferentially processed. These claims were tested by comparing clinically anxious (generalized anxiety disorder [GAD], posttraumatic stress disorder [PTSD]) and clinically depressed children and adolescents on a range of cognitive tasks measuring attention, memory, and prospective cognition, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
123
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(139 citation statements)
references
References 30 publications
9
123
1
4
Order By: Relevance
“…Other studies of attention bias in clinically anxious youth have found an enhanced attention bias towards threat (e.g. Taghavi et al, 1999Taghavi et al, , 2003Dalgleish et al, 2003;Vasey et al, 1995;Waters, et al, 2008). However, there are notable methodological differences between the clinical studies, which may account for much of the variation in their findings (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies of attention bias in clinically anxious youth have found an enhanced attention bias towards threat (e.g. Taghavi et al, 1999Taghavi et al, , 2003Dalgleish et al, 2003;Vasey et al, 1995;Waters, et al, 2008). However, there are notable methodological differences between the clinical studies, which may account for much of the variation in their findings (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are notable methodological differences between the clinical studies, which may account for much of the variation in their findings (e.g. type of attentional task, type of anxiety disorder, presence of clinical depression, severity of anxiety symptoms, experimental conditions; see Dalgleish et al, 2003, Pine, 2007, and Waters et al, 2008, for further discussion). For example, many previous studies have used single words (rather than angry faces) as threat stimuli (e.g., Taghavi et al, 1999Taghavi et al, , 2003Vasey et al, 1995) and have used the modified Stroop task to assess attention bias (e.g., Dalgleish et al, 2003;Taghavi et al, 1999Taghavi et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 presents studies of information processing biases and depression among children and adolescents. Level of depression is associated with greater recall of negative information relative to positive information in youth (Bishop, Dalgleish, & Yule, 2004;Cole & Jordan, 1995;Drummond, Dritschel, Astell, O'Carroll, & Dalgleish, 2006;Rudolph, Hammen, & Burge, 1997;Taylor & Ingram, 1999;Zupan, Hammen, & Jaenicke, 1987; for null results see Dalgleish et al, 2003;and Hammen & Zupan, 1984). This association is also found among children and adolescents with a diagnosis of MDD (Neshat-Doost, Moradi, Taghavi, Yule, & Dalgleish, 2000).…”
Section: An Integrative Perspectivementioning
confidence: 93%
“…Uma questão importante é o quanto um estímulo com valência emocional negativa e alto nível de ativação pode eliciar o viés de atenção em uma amostra sem nenhuma psicopatologia específica (Bar-Haim, Lamy, Pergamin, Bakermans-Kranenburg, & van IJzendoorn, 2007). Alguns estudos nessa área utilizam a Visual Probe Detection Task, para medir o viés de atenção para imagens emocionalmente valentes (Asmundson & Stein, 1994;Dalgleish et al, 2003;Mogg & Bradley, 1998;Taghavi, Neshat-Doost, Moradi, Yule, & Dalgleish, 1999;Vasey, Daleiden, Williams, & Brown, 1995). A tarefa consiste em uma sequência na qual duas imagens são apresentadas em uma tela de computador por curtos intervalos de tempo.…”
unclassified